Evidence of an interaction between nifedipine and nafcillin in humans - Lang, C. C.; Jamal, S. K.; Mohamed, Z.; Mustafa, Mohd Rais; Mustafa, A. M.; Lee, T. C. (Wiley, 2003)
Aims: Nafcillin (Wyeth Laboratories, Philadelphia, PA, USA) has been reported to induce the metabolism of cyclosporin and warfarin, which are known substrates of cytochrome P‐450 (CYP). However, there has not been any report to date on its possible interaction with nifedipine, an index substrate of the enzyme, CYP3A4.